Final exit the practicalities of self-deliverance and assisted suicide for the dying - Humphry, Derek 1930-2025 (Eugene, Or. Hemlock Society, 1991)
The most difficult decision -- Shopping for the right doctor -- Beware of the law -- The hospice option -- The cyanide enigma -- Death-Hollywood style? -- Bizarre ways to die -- The dilemma of quadriplegics -- Self starvation -- The will to die and 'miracle cures' -- Storing drugs -- Who shall know? -- Insurance -- Will there be an autopsy? -- A private affair? -- Support groups for the dying -- Letters to be written -- How do you get the magic pills? -- Self-deliverance via the plastic bag -- Going together? -- When is the time to die -- The final act -- A check list -- Drug dosage table -- Justifiable euthanasia -- A doctor's suicide machine -- Euthanasia by physicians -- Nurses on the frontline -- Methods reviewed -- Bibliographical notes -- Recommended further reading -- The death with dignity act
The most difficult decision -- Shopping for the right doctor -- Beware of the law -- The hospice option -- The cyanide enigma -- Death-Hollywood style? -- Bizarre ways to die -- The dilemma of quadriplegics -- Self starvation -- The will to die and 'miracle cures' -- Storing drugs -- Who shall know? -- Insurance -- Will there be an autopsy? -- A private affair? -- Support groups for the dying -- Letters to be written -- How do you get the magic pills? -- Self-deliverance via the plastic bag -- Going together? -- When is the time to die -- The final act -- A check list -- Drug dosage table -- Justifiable euthanasia -- A doctor's suicide machine -- Euthanasia by physicians -- Nurses on the frontline -- Methods reviewed -- Bibliographical notes -- Recommended further reading -- The death with dignity act.
Includes bibliographical references (p. 172-176) and index
Archivierung prüfen
Keywords: Assisted Suicide; Suicide; Right to die; Euthanasia; Right to die; Suicide; Assisted suicide; Suicide; Right to die